PENINGKATAN PENGETAHUAN TENTANG MEKANISME KOPING ADAPTIF, KESEHATAN TIDUR DAN KESEHATAN GIGI DAN MULUT ANAK SEKOLAH - Eka Wahyuningrum; Natalia Ratna Yulianti; Andri Kenti Gayatina (P3M Universitas Aisyiyah Surakarta, 2020)
Background: Preliminary studies found variations in sleep habits, coping mechanism and cavities and dirty teeth on school-age children. Resolving health problems that occur in children requires a family center care approach. Objective: Increasing parental knowledge about sleep health and adaptive coping mechanism of children and increasing children’s knowledge about oral health. Method: This activity is carried out for 3 days. The first day and third day counseling about sleep health and dental and oral health for children through snakes and ladder’s game and video of tooth brush and sleep. Activity on second day was counseling to all parents of school children about adaptive coping mechanism and children's sleep health. Based on observations on these activities, several positive impacts were found including; 1)Children and parents were involved in activities, all children were involved and more than 50% of parents participated in the activity, 2)The child looks enthusastic of the games and videos that were shown, parents looked enthusiastic asking during the counseling. Results: There were significant increasing knowledge in children about oral health and significant increasing knowledge in parents immediately after counseling and decreasing knowledge after 3 months posttest. Conclusion: Counseling to parents and children were increasing knowledge soon after counseling.